TINJAUAN HUKUM HUBUNGAN KEMITRAAN ANTARA EKSEKUTIF DAN LEGISLATIF DALAM PENYELENGGARAAN PEMERINTAHAN DAERAH - Nila Trisna (Universitas Teuku Umar, 2017)
The Regional People's Legislative Assembly (DPRD) is a form of representative institution of the people of provinces, districts, or cities in Indonesia which is located as an element of local government administration together with the Regional Government. The existence of the Regional People's Legislative Assembly is regulated, among others, in Law Number 27 Year 2009 concerning the People's Consultative Assembly, the People's Legislative Assembly, the Regional Representative Council, and the Regional People's Legislative Assembly. Article 342 of Law Number 27 Year 2009 stipulates that